Where goodness still grows : reclaiming virtue in an age of hypocrisy - Peterson, Amy, 1981- (W Publishing Group, an imprint of Thomas Nelson, 2020)
"Where Goodness Still Grows dissects the moral code of American evangelicalism and puts it back together in a new way. Amy writes as someone intimately familiar with, fond of, and also deeply critical of the world of conservative evangelicalism. She writes as a woman and a mother, as someone invested in the future of humanity, and as someone who just needs to know how to teach her kids what it means to be good. She reimagines virtue as a tool, not a weapon; as wild, not tame; as embodied, not written. Reimagining specific virtues, such as kindness, purity, modesty, hospitality, and hope, Amy finds that if we listen harder and farther, we will find the places where goodness still grows"--